Preferensi Wisatawan Muslim Dalam Memilih Restoran Di Kelurahan Kuta Kabupaten Badung - Anisa Devi Damayanti; Agus Muriawan Putra; Ni Nyoman Sri Aryanti (Jurnal Kepariwisataan dan Hospitalitas, 2018)
The domestics muslim traveler needs of food and drinks during the touristic travel requires specific criteria. The domestics muslim traveler prefer the restaurant which have halal sertificate. Domestics Muslim traveller who visit the Kuta Village are fced with many restaurant available there. The study aims to determine the preferences of domestics muslim traveler in choosing a restaurant in Kuta Village. The technique of determination the sample using the te qouta sampling technique with the number of samples of 100 respondents and sampling techniques using incidental sampling (domestics muslim travelers ever come to Kuta Village and enjoy the restaurants in Kuta Village). The data analysis in this study used qualitative analysis techniques and conjoin analysis with the help of Statistical Product and Service Solution (SPSS) version 23. The results of this research show that the domestics muslim travellers in selecting preference restaurant of attributes and the level attribute the highest is the price of restaurant menu is priced at Rp 50,000 – Rp 100,000 for main dishes, the kind of restaurants is informal, menu of restaurants is Ala Carte, the atmosphere of restaurant is traditional and service of restaurant is Table Service. The results also show the correlation estimation and actual have a very strong relationship and the significance of the relationship attribute and attribute levels have a strong relationship. Keyword : Preference, Muslim Traveller, Restaurant.